21 of 2321 of 23 Items

19:35

















































































Question
Consider the sequence of steps to solve the equation: 3(x − 4) + 5x = 9x − 36

Given ⇒ 3(x − 4) + 5x = 9x − 36
Step 1 ⇒ 3x − 12 + 5x = 9x − 36
Step 2 ⇒ 3x + 5x − 12 = 9x − 36
Step 3 ⇒ 8x − 12 = 9x − 36
Step 4 ⇒ 8x − 8x − 12 = 9x − 8x − 36
Step 5 ⇒ 0 − 12 = x − 36
Step 6 ⇒ −12 = x − 36
Step 7 ⇒ −12 + 36 = x − 36 + 36
Step 8 ⇒ 24 = x + 0
Step 9 ⇒ 24 = x

Which property yields Step 6?
Responses
A Additive Inverse PropertyAdditive Inverse Property
B Additive Identity PropertyAdditive Identity Property
C Addition Property of EqualityAddition Property of Equality
D Commutative Property of Addition

1 answer

B Additive Identity Property
Similar Questions
  1. Civics Unit Test21 of 2321 of 23 Items Question Use the pronunciation guide for the word camel to answer the question. ˈka-məl
    1. answers icon 1 answer
  2. 3 of 33 of 3 ItemsQuestion Note: Enter your answer and show all the steps that you use to solve this problem in the space
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 3 answers
more similar questions